Implications of impacted mandibular cuspids on mental foramen position - A.K. Nagarajappa; M.K. Alam; A.A. Alanazi; V. Bandela; S. Faruqi (Elsevier, 2021)
Objective: To determine the horizontal and vertical locations and dimensions of the mental foramen (MF) in digital panoramic images (DPI), and to evaluate the effect of impacted mandibular cuspids (IMC) on the position of the MF. Materials and Methods: 715 Digital panoramic images were obtained from the archives of oral radiology clinics of the College of Dentistry, Jouf University. Altogether 236 DPI that met inclusion and exclusion criteria were investigated. One specialist principal investigator examined and analyzed the DPI on a computer screen for horizontal location, average position, and vertical location of the MF. Results: The most common horizontal location of MF with the apices of the teeth in the non-impacted group (NIG) was found to be c = 64.70%, and in the impacted group (IG) d = 47.10%. The average magnitude of MF relative to the apex of second bicuspid in the NIG was found to be 47.10% on the mesial side, and in IG 44.10% on the distal side. The average vertical distance of MF from the lower border of the mandible to the lower border of MF (DLM) in NIG was 14.13 mm (SD ± 1.75 mm), and in IG was 16.85 mm (SD ± 3.06 mm). The average vertical distance of MF from the alveolar crest to the superior border of MF (DAC) in NIG was 6.56 mm (SD ± 2.02 mm), and in IG was 6.67 mm (SD ± 2.28 mm). Conclusion: The impacted mandibular cuspid has a definite influence on the location and position of the MF.